Проблеми фінансування охорони здорв’я в Україні - Левчук, Н.М. (Інститут демографії та соціальних досліджень НАН України, 2008)
В работе рассматриваются основные проблемы финансирования здравоохранения в Украине и обосновываются пути реформирования механизма финансового обеспечения медицинской отрасли. The basic problems of public health sector financing in Ukraine are reviewed and the approaches for reforming the financial mechanism of health sector are described in this work.